Development of Mimokines, chemokine N terminus-based CXCR4 inhibitors optimized by phage display and rational design. Issue 2 (23rd March 2018) - Fievez, Virginie; Szpakowska, Martyna; Mosbah, Amor; Arumugam, Karthik; Mathu, Julie; Counson, Manuel; Beaupain, Nadia; Seguin-Devaux, Carole; Deroo, Sabrina; Baudy-Floc'h, Michèle; Chevigné, Andy
Abstract: The chemokine receptor CXCR4 (C-X-C chemokine receptor type 4 also known as fusin or CD184 (cluster of differentiation 184)) is implicated in various biological and pathological processes of the hematopoietic and immune systems. CXCR4 is also one of the major coreceptors for HIV-1 entry into target cells and is overexpressed in many cancers, supporting cell survival, proliferation, and migration. CXCR4 is thus an extremely relevant drug target. Among the different strategies to block CXCR4, chemokine-derived peptide inhibitors hold great therapeutic potential. In this study, we used the N-terminus of vCCL2/vMIPII, a viral CXCR4 antagonist chemokine, as a scaffold motif to engineer and select CXCR4 peptide inhibitors, called Mimokines, which imitate the chemokine-binding mode but display an enhanced receptor affinity, antiviral properties, and receptor selectivity. We first engineered a Mimokine phage displayed library based on the first 21 residues of vCCL2, in which cysteine 11 and 12 were fully randomized and screened it against purified CXCR4 stabilized in liposomes. We identified Mimokines displaying up to 4-fold higher affinity for CXCR4 when compared to the reference peptide and fully protected MT-4 cells against HIV-1 infection. These selected Mimokines were then subjected to dimerization, D-amino acid, and aza-β3-amino acid substitution to further enhance their potency and selectivity. Optimized Mimokines exhibited up to 120-fold enhanced CXCR4 binding (range of 20 nM) and more than 200-fold improved antiviral properties (≤ 1 μM) compared to the parental Mimokines. Interestingly, these optimized Mimokines also showed up to 25-fold weaker affinity for ACKR3/CXCR7 and may therefore serve as lead compounds for further development of more selective CXCR4 peptide inhibitors and probes. Development of CXCR4 peptide inhibitors with enhanced receptor affinity/selectivity and antiviral properties.